Occupational Hazards and Health Problems among Butchers in Uyo, Nigeria - Johnson, Ofonime Effiong (Niger Med J, 2019)
INTRODUCTION: Butchers are exposed to various types of hazards in the course of their work, which could lead to health problems of varying severity. The aim of this study was to identify the occupational hazards and health problems of butchers in Uyo and also assess the physical conditions of their slaughter facilities. MATERIALS AND METHODS: A descriptive cross-sectional study was carried out among 157 butchers in Uyo using a semi-structured questionnaire for data collection. Facility assessment was made using a checklist. Analysis was carried out using Statistical Package for Social Sciences version 20. Level of significance was set at 0.05. RESULTS: The mean age of respondents was 33 ± 9.94 years. Most respondents were males (83.4%). The most commonly reported workplace hazards were knife (93.6%), bones (57.3%), and slippery floor (24.8%). The most common health problems were knife cuts (87.3%), cuts from bones (50.3%), and neck pain (36.9%). Having injuries from live animals and back pain were significantly associated with working with cows (P < 0.05). The most common de-furring method was burning with firewood (61.1%). The slaughter facilities lacked many expected amenities of a standard abattoir. CONCLUSION: Identified hazards and health problems of butchers were numerous. The slaughter facilities lacked appropriate equipment that promotes workers’ health and safety. It is recommended that slaughter facilities be upgraded to meet the standard abattoir practice. Regular training of butchers should be organized by their association to encourage safer practice, including the use of appropriate protective wears. Use of the chemical method of de-furring should also be encouraged to limit exposure to harmful gases.